Appropriating Islam as a Matrix - Barylo, William (Method & theory in the study of religion, 2017)
Observing and interviewing Muslim volunteers involving themselves in European charities with a strong religious frame reveals that Islam is more than rituals and beliefs but a complex system of ideas providing an original perception of the society, the environment and the individual. Therefore, the terms and categories gravitating around “religion” appear limited when trying to define Islam accurately for social sciences. The way Muslim volunteers practice their Islam is not limited to ritual performance; they try to find practical implementations of the ethics of Islam in areas like banking, charity, consumerism or democracy. These volunteers blur the boundaries of the concepts of “sacred” and “mundane,” thereby redrawing the limits of what is “religious” and what is not. After discussing the limits of the category of “religion” for describing Islam, this article follows French sociologist Edgar Morin’s theory of complex systems, suggesting the study of Islam as a matrix. On a wider perspective it will aim to bridge conceptual gaps in the study of religions, trying to find a more flexible concept that can also apply to other systems of ideas, cultures, beliefs and principles.